Predicting immune-related adverse events in patients with melanoma: the role of interleukin-7 rs16906115 polymorphism and lymphocyte dynamics - Açar, Fatma Pınar; Acar, Caner; Gunenc, Damla; Arisoy, Çağlar; Ece Solmaz, Asli; Gecgel, Asli; Yüksel, Haydar Çağatay; Şahin, Gökhan; Ozkan, Oguzcan; Gokdere, Zeynep Sila; Duman, Nilay; Karaca, Burçak (Frontiers in Immunology, 2025)
IntroductionImmune checkpoint inhibitors (ICIs) have transformed the therapeutic landscape of malignant melanoma; however, they are frequently associated with immune-related adverse events (irAEs). Emerging evidence suggests that genetic predispositions, including interleukin-7 (IL-7) gene variants, may influence the risk of these toxicities.MethodsIn this single-center retrospective study, we investigated the potential utility of IL-7 rs16906115 polymorphism and lymphocyte stability index (LSI) in predicting susceptibility to irAEs among 96 melanoma patients treated with ICIs.ResultsGenotyping revealed a minor allele frequency of 8.3% for rs16906115. Logistic regression analysis indicated that carriers of the minor allele had a significantly increased risk of all-grade irAEs compared to reference allele carriers (adjusted OR: 3.93; 95%CI:1.13–13.64; p=0.031). Subgroup analyses revealed a significant increase in risk across endocrine, non-cutaneous, multiple, low-grade, and early onset (<3 months) irAEs. While neither baseline lymphocyte count nor LSI predicted overall irAE incidence, an elevated LSI emerged as a key risk factor for early steroid-requiring irAEs (adjusted OR:3.79; 95% CI: 1.14–12.61; p =0.030).DiscussionThese findings from a Turkish cohort corroborate earlier European studies suggesting that rs16906115 minor allele carriage may be a genetic risk factor for irAEs. Furthermore, LSI may serve as a dynamic biomarker for predicting early steroid-requiring irAEs. Prospective multicenter studies among diverse populations are warranted to validate these findings.